THE PHARMACOLOGICAL CHARACTERISTIC OF SEDATIVE PREPARATIONS - Sevastyanova, T.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
In the present review is displayed the pharmacological characteristic of modern representatives of group of sedative medicines, and those belong to the group, applied for a long time in a medical practice. Pharmacological marketing and the comparative characteristic of sedatives will help the doctor make the beast choice.